2019
DOI: 10.1177/0309324719847069
|View full text |Cite
|
Sign up to set email alerts
|

Cushioning energy absorption of composite layered structures including paper corrugation, paper honeycomb and expandable polyethylene

Abstract: The composite layered structures including paper corrugation, paper honeycomb and expandable polyethylene are innovative structures of cushioning energy absorption, and the compression and impact resistances of the expandable polyethylene can be enhanced by laminating the corrugated paperboard or honeycomb paperboard. This article evaluated the compression performance and cushioning energy absorption of the composite layered structures by the static compression and drop impact compression tests. On one hand, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Figure 7 depicts that the impact energy loss has a linear relationship with drop height at the same number of drops and drop orientation. Guo et al 46 have also found that there is a linear relationship between the energy absorption characteristics of BC/EPE structures and the initial impact energy, which echoes the findings in this paper. Additionally, there is a linear relationship between the initial impact energy and the drop height since air resistance is not considered.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Figure 7 depicts that the impact energy loss has a linear relationship with drop height at the same number of drops and drop orientation. Guo et al 46 have also found that there is a linear relationship between the energy absorption characteristics of BC/EPE structures and the initial impact energy, which echoes the findings in this paper. Additionally, there is a linear relationship between the initial impact energy and the drop height since air resistance is not considered.…”
Section: Resultssupporting
confidence: 90%
“…When the number of drops at the corner (Figure 10G,H) increases to the fourth, the COR fluctuates about 8% due to a slight tear in the cushion. Moreover, the first impacts of Flat 5 at 13°C and 50% RH (Figure 10B) and Edge 12 at 33°C and 50% RH and 23°C and 80% RH (Figure 10D) fluctuate greatly, with a maximum of 12.8%, which may be due to individual differences in the corrugated carton or cushion 46 . It can be concluded that the effect of temperature and humidity on COR is less than 5% relative to the control group.…”
Section: Resultsmentioning
confidence: 93%
“…After substituting equation (9) into equation (8), the propagation law for the first waveform amplitude stress of the elastic wave in square-packed circular honeycombs can be expressed as…”
Section: Determination Of Elastic Wave Amplitudementioning
confidence: 99%
“…[1][2][3][4][5] In addition to mechanical properties, the cellular solids with unified microstructure have functional properties (such as thermal insulation, sound absorption, and invisibility) and have been extensively explored by numerous scholars. [6][7][8][9] Extension for the applications of intelligent materials, bio-mimetic materials, and composites and advances in industrial technologies (such as freeze-cast, additive manufacturing, and nanotechnology) have recently made the trend that combining emerging materials with porous structures to develop functional metamaterials with certain mechanical properties. 10,11 Lurie et al 12,13 performed theoretical analysis and numerical simulation in order to optimize the microstructure variables of the corrugated-core sandwich panels; thermal barrier skins with best combinations of the thermal and mechanical performances under extreme temperature conditions were designed.…”
Section: Introductionmentioning
confidence: 99%
“…The modal response of a corrugated composite sandwich cylindrical panel that filled with foam was studied by Yang et al 21 They showed that natural frequency of foam filled samples have no significant change compared with samples without foams but structural damping is improved. Guo et al 22 studied energy absorption and impact behavior of composite laminates including corrugation, honeycomb and expandable polyethylene. They concluded that corrugation and honeycomb have better energy absorption compared to expandable polyethylene.…”
Section: Introductionmentioning
confidence: 99%